City-district divergence grid: A multi-level city brand positioning tool - Viriya Taecharungroj (2019)
© 2017 Macmillan Publishers Ltd. City brand positioning is a major challenge in the branding efforts of cities and places. The purpose of this research is to examine various place branding concepts and create a management tool that can help city administrators develop city brand positioning strategies. This research also used the tool to evaluate and identify an appropriate city brand positioning strategy for Bangkok. The author collected data from 789 residents in ten districts of Bangkok in June 2016. A paired sample t test analysis was used to plot the results of the proposed tool. The city-district divergence grid is a multi-level tool that evaluates the attributes and personality of a city and its sub-units or districts. It also provides city administrators with the most suitable characteristics for city and district positioning to appeal to their main customers - residents. After analysing the data, the proposed tool suggests that the Bangkok Metropolitan Administration (BMA) should employ sub-brand or endorsed brand strategies because most districts reside in the middle of the grid. The use of sub-brands or endorsed brand strategies can highlight Bangkok's strong economy and active personality. City administrators can then develop individual district brands based on their distinct characteristics.